Echocardiographic determinants of LV functional improvement after transcatheter aortic valve replacement. Issue 6 (19th November 2015) - Chen, Jinling; Nawaz, Nasir; Fox, Zachary; Komlo, Caroline; Anwaruddin, Saif; Desai, Nimesh; Jagasia, Dinesh; Herrmann, Howard C.; Han, Yuchi
Abstract : Background: Transcatheter aortic valve replacement (TAVR) is an established therapy in high‐risk patients with severe aortic stenosis. Among patients with reduced left ventricular ejection fraction (LVEF), it is unclear which patients will derive maximal benefit from TAVR. Methods: Clinical and echocardiographic data of patients with severe aortic stenosis and low LVEF (≤50%) who underwent TAVR at a single institution during 2009–2013 were retrospectively analyzed. Patients were divided into 2 groups post‐TAVR based on improved LV function (Group A = ΔLVEF ≥ 10%) versus persistent LV dysfunction (Group B = ΔLVEF<10%). Echocardiographic parameters were assessed for their association with LVEF change post‐TAVR. Kaplan–Meier analysis was performed to generate survival estimates. Results: Of 382 patients who underwent TAVR, 60 patients had low LVEF, LV function failed to improve ≥10% in 50% of patients following the procedure (Group B). At baseline echocardiograms, Group B had higher LVEF, stroke volume (SV), SV index; and lower E, E/E′, and estimated pulmonary arterial systolic pressure (PASP) compared to Group A. Higher mortality was found in Group B compared to the Group A ( p = 0.003) with a significantly shorter survival (Group A = 3.3 ± 0.1 years vs Group B = 2.7 ± 0.2 years, p = 0.003). One‐year event free survival was 53.3% in Group B compared to 93.3% in Group A, with a stable trend over ensuing years (5‐year survival; 53.3% versus 90.0%, p = 0.003). Conclusions: In patients undergoing TAVR with depressed LV function, those who failed to improve were more likely to have relatively higher LVEF, SV, and SVI; and lower E, E/E′, and PASP at baseline. Mortality rates were found to be higher in persistent LV dysfunction group. © 2015 Wiley Periodicals, Inc.